PENGARUH MEDIA VIDEO ANIMASI TERHADAP PEMAHAMAN KONSEP IPA SISWA KELAS IV SEKOLAH DASAR - Azzahra, Fernita Dwi; Rini, Candra Puspita; Oktrifianty, Erdhita (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2024)
Many elementary school students have low conceptual understanding, it is because students do not absorb learning well, and one of the factors is the lack of learning media. Therefore, it is necessary to use more interactive learning media such as animated video media. This study aims to determine the effect of animated video media on students' understanding of science concepts. This research was conducted at SDN Kebon Besar 1. The method applied in this study is quantitative in the form of quasi-experiments. The population of this study was all grade IV students totaling 56 students, which were divided into two (2), namely class IVA as a control class using conventional learning methods and class IVB as an experimental class using animated videos. The data collection technique was in the form of a test (pretest-posttest). Hypothesis testing carried out with a t-test on the posttest test with a significance level of ? = 0.05 found Sig. (2-tailed) = 0.000 which means H0 is rejected and H1 is accepted. It can be concluded that animated video media has an effect on students' understanding of science concepts.